Organizational structure, human resource practices, organizational culture and innovation activity among small and medium-sized enterprises in Algeria - Gougui, Ayoub (2017)
Despite the importance of innovation to small and medium-sized enterprises (SMEs), the review of the literature and past studies indicate that there are not many studies that have investigated organizational factors associated to innovation activity among SMEs, particularly in the Algerian context. As a result, there is little information about the linkage between organizational factors and innovation activity in Algerian SMEs. Given the research gap and limited information, this study attempted to investigate the relationships between organizational structure, human resources practices, organizational culture and innovation activity in Algerian SMEs. By using structured questionnaire, the data for the study was gathered from 77 SMEs operating in the manufacturing sector in the southern region of Algeria. The Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze the data and test the hypotheses developed in the study. The results of the study indicate that organizational structure and organizational culture were significantly related to the innovation activity of the SMEs in the study. However, the results show not significant relationship between human resource practices and innovation activity.